Oral vitamin D supplementation is associated with full enteral feeding in very low birth weight infants - Yie Huang; Ping Zhou; Ruiping Wu; Xiaomei Fan; Ping Zheng; Xintian Shen (The Journal of Maternal-Fetal & Neonatal Medicine)
Background and aims As vitamin D is mostly transferred to the fetus during the third trimester, preterm infants are born with lower vitamin D stores. However, most clinical guidelines do not suggest clearly when to initiate vitamin D in very low birth weight (VLBW) infants. This retrospective study aimed to assess whether the initiation of oral vitamin D supplementation was associated with full enteral feeding (FEF) in VLBW infants.Methods A total of 383 VLBW infants (gestational age, 24–32 weeks; birth weight, 570–1500 g) admitted to our neonatal intensive care unit between October 2018 and December 2022 were included in this study. To assess the independent association between oral vitamin D and FEF, univariate or multivariate Cox analyses were performed, adjusting for 16 major confounders (birth weight, initiation of enteral feeding, sepsis, the enteral feed volume when oral vitamin D started, etc.). Time-varying coefficients method is used to accommodate the non-constant hazard ratio implied by the proportional hazards assumption violation.Results Multivariate Cox regression for the time to reach full enteral feeding (T-FEF) and time to add human milk fortifier (T-HMF) were analyzed respectively. Delayed oral vitamin D supplementation (after postnatal day 13) was independently and negatively associated with the cumulative probability of achieving FEF (B − 5.088, RR 0.006 (0.001–0.057), p < .00001). Delayed oral vitamin D supplementation was independently and negatively associated with the cumulative probability of adding human milk fortifier (HMF) (B − 3.115, RR 0.044 (0.006–0.334), p = .002). The hazard effect of the delayed supplementation diminished over time, with the RR = EXP(−5.088 + 1.447 × Ln(T-FEF)) or RR = EXP(−3.115 + 0.729 × Ln(T-HMF)), respectively.Conclusions Our research suggests that earlier initiation of oral vitamin D is associated with improved FEF in VLBW infants.